An analysis of model testing and finite element approach for distribution of earth pressures - Jungang Liu; Feng Liang; Geng Chen (Alexandria Engineering Journal)
This study presents a comprehensive comparison of laboratory experiments and numerical simulations using finite element analysis (FEA) to investigate the effects of various geotextile spacing on the distribution of earth pressure. The experiments were conducted in the ''Tiger Cage (TC)'' testing facility at the University of Colorado Denver's (UCD) Geotechnical Engineering Science Center. A total of four large-scale tests were performed on Leyden Clay (LC) and Colorado Department of Transportation Class 1 Structure Backfill Material (CDOT Class 1 SBM) to validate the finite element model. The research focuses on the distribution of earth pressure on Leyden Clay and CDOT Class 1 SBM, validated through large-scale physical tests and 3D FEA simulations performed using the LS-DYNA and ABAQUS software. The results demonstrate the accuracy of numerical models in predicting earth pressure distributions, with strong correlations observed between experimental data and simulation results. The study reveals that the current method provision is inaccurate in predicting earth pressure distribution at the bottom of the wall, as the predicted data from numerical models show the highest earth pressures of 485Kpa around two-thirds of the wall height (150 cm). This research provides valuable insights into soil-structure interaction, contributing to the design and analysis of retaining walls and foundations in geotechnical engineering.